A review of modeling techniques and structural topologies for double stator permanent magnet machines - Muliawati, Fithri; Ahmad, Suhairi Rizuan Che; Othman, Raja Nor Firdaus Kashfi Raja; Yahya, Yanawati; Nur, Tajuddin (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
This study reviews the advancements in double-stator permanent magnet machines (DSPMM) with a focus on modeling techniques, design variations, and performance optimization. The research categorizes existing DSPMM modeling methods, including numerical approaches like finite element method (FEM) and boundary element method (BEM), as well as analytical approaches such as analytical subdomain method (ASM), magnetic equivalent circuit (MEC), and Maxwell's equation approach (MEA). These methods improve analytical accuracy, computational efficiency, and address challenges like magnetic saturation and electromagnetic interactions. Structural innovations, including segmented rotor-stator techniques, Halbach arrangements, and soft composite materials, enhance torque density, reduce cogging torque, and optimize magnetic flux distribution, contributing to higher energy efficiency and reduced noise. Supported by software tools like Ansys Maxwell and JMAG-designer, this study identifies optimal DSPMM configurations for various applications, including electric vehicles and renewable energy systems. The findings emphasize the potential of DSPMM for efficient, high-performance electric machines while highlighting the need for further research on transient effects and advanced cooling systems to improve thermal stability.